Optimum Sustainable Mix Proportions of High Strength Concrete by Using Taguchi Method (Fracture and Structural Integrity, 2020)
In this study, mix proportion parameters of high strength concrete (HSC) were analyzed by using the Taguchi’s experiment design methodology for optimal design. For that purpose, mixtures are designed in a L27 orthogonal array with six factors, namely, ‘Silica Fume’, ‘Steel Fiber’, ‘Super-Plasticizer’, ‘Maximum Aggregate Size (AG)’, ‘Water / cementitious material (W/C) ratio’, ‘Fly Ash’. The mixtures were extensively tested to meet technical requirements of HSC. The experimental results were analyzed by using the Taguchi experimental design methodology. The best possible levels for mix proportions were determined for maximization of compressive strength at 7, 28, 56, 90 days, splitting tensile strength at 28 days, flexural strength at 28 days, and the slump. Also the best possible levels for mix proportions were determined for minimization of the production cost. It was found that steel fibers and fly ash are the most dominant factors in the process of optimization. The advantage of using steel fiber and fly ash was the reduced energy and cost associated with the raw materials which meant more sustainable concrete could be attained. It was also found that there is a necessity to apply a multi- response optimization to get the best mix proportions.
Keywords: High strength concrete; Taguchi method; Optimal mix design